Competitive Analysis of The Sumatra Rubber Industry in Asean Free Market - Widyastutik (Jurnal Manajemen dan Agribisnis, 2020)
The objectives of this research are to analyze (1) competitiveness and potential market attractiveness and business strength of rubber Sumatran in the ASEAN Market (2) Factors affect the Sumatran rubber industry competitiveness in the ASEAN market. The type of data used for this research development is primary and secondary data. Primary data were obtained from stakeholders, both exporters and producers in the rubber industry around North Sumatra and Riau. This research is using EPD and SEM PLS analysis methods. The Results of the RCA index shows that Indonesia ranks second after Vietnam for competitiveness. EPD analysis method shows that rubber and other rubber products are on the Lost Opportunity position in the ASEAN market. On the other hand, SEM PLS shows that in six latent variables, there are four variables that have an impact on Sumatran rubber industry competitiveness, two variables have a positive effect while the other two variables have a negative effect. Keywords: rubber Sumatran, ASEAN Market, competitiveness and potential market, SEM PLS, RCA